Kuasa-kuasa budi bicara teori dan pemakaiannya dalam undang-undang perlembagaan dan undang-undang pentadbiran - Abdul Aziz Bari, (Fakulti Undang - Undang, 2004)

(untitled)
This article seeks to examine the essence of discretionary powers in both constitutional and administrative laws. It appears that the case law and scholarly views consider those powers similar. This is arguably untenable for in constitutional law most of what are called discretionary powers are not always the case: it very much depends on the circumstances and the guiding principle for the exercise of discretionary power in constitutional law is largely democratic ideas. In administrative law however such principle is not too evident. Interestingly enough however the case law has introduced various doctrines and principles which are actually democratic in their essence